World Christianity: methodological considerations - Frederiks, Martha Theodora; Nagy, Dorottya (Theology and mission in world christianity, 2021)
"World Christianity publications proliferate but the issue of methodology has received little attention. World Christianity: Methodological Considerations addresses this lacuna and explores the methodological ramifications of the World Christianity turn. In twelve chapters scholars from various academic backgrounds (anthropology, religious studies, history, missiology, intercultural studies, theology, and patristics) as well as of multiple cultural and national belongings investigate methodological issues (e.g. methods, use of sources, choosing a unit of analysis, terminology, conceptual categories,) relevant to World Christianity debates. In a closing chapter the editors Frederiks and Nagy converge the findings and sketch the outlines of what they coin as a 'World Christianity approach', a multidisciplinary and multiple perspective approach to study Christianity/ies' plurality and diversity in past and present"--